ANALISIS KEMANDIRIAN FISKAL, KETERGANTUNGAN FISKAL DAN EFEKTIVITAS FISKAL PROVINSI D.I YOGYAKARTA TAHUN 2018-2022 - Kumba Digdowiseiso; Dhimas Kaliwattu (Jurnal Ilmiah Global Education, 2023)
This study aims to analyze Fiscal Independence, Fiscal Dependence and Fiscal Effectiveness of the D.I Yogyakarta Province in the 2018-2022 period. The research is quantitative descriptive by observing the posture of the provincial budget. In the aspect of fiscal independence, an average value of 36.7 is obtained, including the category towards independence. In the aspect of fiscal dependence, the value tends to be > 50 with an average percentage of 62.9 percent, including in the very high category. In the aspect of fiscal effectiveness, the figure obtained was 104.39 percent, including the category of very effective fiscal implementation in the region. Based on the review in this study, which found fluctuating changes from year to year, it justifies the influence of the First-Generation Theory that the central government's intervention to the Provincial Government of the Special Region of Yogyakarta still has a significant influence on regional fiscal independence, dependence and effectiveness.